TINJAUAN ATAS CASH CALL DAN JOINT INTEREST BILLING (JIB) PADA BADAN OPERASI BERSAMA PT BUMI SIAK PUSAKO - PERTAMINA HULU - Syarifah Hafizah, (2020)
This Final Project tells about the observation of cash call and Joint Interest Billing (JIB) in the joint operating body (JOB) of PT Bumi Siak Pusako - Pertamina Hulu. JOB Of PT Bumi Siak Pusako Pertamina Hulu is one from of Joint Operation (JO) between central government is represented by Pertamina Hulu and PT Bumi Siak Pusako as a deputy from regional government with oil and gas contractor in Indonesia. Joint Operation (JO) produces 2 (two) Joint Operation Contract (JOC) is Production Sharing Contract (PSC) and Joint Operation Agreement (JOA). Production Sharing Contract (PSC) is agreement between oil and gas contractor with Indonesian's government. While, Joint Operation Agreement (JOA) is agreement between oil and gas contractor with oil and gas industry hulu. The main funding source for financing operations and petroleum activities is a cash call from PT Siak Pusaka and Pertamina Hulu as a partner. JOB PT Bumi Siak Pusako - Pertamina Hulu is an operator from upstream oil activities obliged to make reports related to developments from the oil operations and accountability for cash call funds to partners, Joint Interest Billing (JIB) form. Joint Interest Billing (JIB) consists of 4 (four) reports: Lifting Summary, Share Calculation, Work Program and Budget Realization, and Cost Recovery.